The True Self. Critique, Nature, and Method - Sparby, Terje; Edelhäuser, Friedrich; Weger, Ulrich W. (Frontiers in Psychology, 2019)
The history of philosophy gives us many different accounts of a true self, connecting it to the essence of what a person is, the notion of conscience, and an ideal human being. Some true self-proponents can also be found within psychology, but its existence is mostly rejected. However, many psychological studies have shown that people commonly believe in the existence of a true self. Hence, although folk psychology often includes a belief in a true self, its existence is disputed by psychological science. Here we consider the critique raised by Strohminger, Newman, and Knobe, stating that the true self is (1) radically subjective and (2) not observable, and hence cannot be studied scientifically (Strohminger, Knobe, & Newman, 2017). On closer investigation, the argument that the self is radically subjective is not convincing. Furthermore, rather than accepting that the true self cannot be studied scientifically, we ask: What would a science have to look like that would be able to study the true self? In order to answer this question, we outline the conceptual nature of the true self, which involves phenomenological and narrative aspects in addition to psychological dimensions, and suggest a method through which this concept can be investigated from the first-person perspective.